2001
DOI: 10.1061/(asce)0733-947x(2001)127:4(269)
|View full text |Cite
|
Sign up to set email alerts
|

Ground-Penetrating Radar for Cold In-Place Recycled Road Systems

Abstract: Saskatchewan Department of Highways and Transportation (SDHT) is responsible for maintaining approximately 6500 kilometers of northern gravel surfaced roads. Many of these northern gravel roads are built on poorly graded sand subgrades and may contain protruding bedrock and/or large boulders. Because of this, washboarding, protruding rocks, rutting and potholes are common performance problems of many northern gravel roads. Routine blading of these roads is often ineffective because unstable sand does not maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…divide road into homogenous sub-sections, or to check if the pavement is thick enough for recycling milling and (4) for quality control purposes (see Briggs et al, 1991;Fernando et al, 1994;Saarenketo, 1997;Saarenketo and Roimela, 1998;Scullion and Saarenketo, 1998;Berthelot et al, 2001;Maser, 2002b;Saeed and Hall, 2002;Sebesta and Scullion, 2002a,b;Hugenschmidt, 2003;Noureldin et al, 2003). divide road into homogenous sub-sections, or to check if the pavement is thick enough for recycling milling and (4) for quality control purposes (see Briggs et al, 1991;Fernando et al, 1994;Saarenketo, 1997;Saarenketo and Roimela, 1998;Scullion and Saarenketo, 1998;Berthelot et al, 2001;Maser, 2002b;Saeed and Hall, 2002;Sebesta and Scullion, 2002a,b;Hugenschmidt, 2003;Noureldin et al, 2003).…”
Section: Bituminous Pavement Thickness and Moisturementioning
confidence: 99%
“…divide road into homogenous sub-sections, or to check if the pavement is thick enough for recycling milling and (4) for quality control purposes (see Briggs et al, 1991;Fernando et al, 1994;Saarenketo, 1997;Saarenketo and Roimela, 1998;Scullion and Saarenketo, 1998;Berthelot et al, 2001;Maser, 2002b;Saeed and Hall, 2002;Sebesta and Scullion, 2002a,b;Hugenschmidt, 2003;Noureldin et al, 2003). divide road into homogenous sub-sections, or to check if the pavement is thick enough for recycling milling and (4) for quality control purposes (see Briggs et al, 1991;Fernando et al, 1994;Saarenketo, 1997;Saarenketo and Roimela, 1998;Scullion and Saarenketo, 1998;Berthelot et al, 2001;Maser, 2002b;Saeed and Hall, 2002;Sebesta and Scullion, 2002a,b;Hugenschmidt, 2003;Noureldin et al, 2003).…”
Section: Bituminous Pavement Thickness and Moisturementioning
confidence: 99%
“…Due to its increasingly widespread application worldwide [8][9][10][11][12][13][14][15], numerous studies have shown that the process of curing and adhesion development of CR mixtures are key issues in this field. The development of adhesion is a prerequisite for its strength formation, and its strength is an important basic mechanical indicator in its application.…”
Section: Introductionmentioning
confidence: 99%